Effect of capital intensity on corporate income tax payable / Ninda Setiani, Any Eliza and Rosydalina Putri - Setian, Ninda; Eliza, Any; Putri, Rosydalina (Universiti Teknologi Mara Selangor, 2023)
Corporate Income Tax Payable is a tax imposed on income earned by business entities in one year. Many factors can affect corporate income tax. This study aims to analyze the effect of operational costs, profitability, and capital intensity on corporate income tax payable. The companies studied were food and beverage sub-sector companies listed on the Indonesian Sharia Stock Index (ISSI) with a sample of 20 companies for three years, the 2019-2021 period. The method used in this study is multiple linear regression analysis with the help of the SPSS 23 program. The data collection technique was carried out using documentation techniques with secondary data types, namely in the form of financial statements of food and beverage sub-sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the period 2019-2021. The results of this study indicate that operational costs have a positive effect on corporate income tax payable, profitability has a positive effect on corporate income tax payable and capital intensity has no effect on corporate income tax payable.